Adolescent violence towards parents—Prevalence and characteristics using Australian Police Data - Moulds, Lauren (The Australian and New Zealand journal of criminology, 2019)
Adolescent violence toward parents is a unique form of family violence which for many, including police personnel, challenges traditional views of parent-child relationship, and raises questions about victimization. There has been minimal research in Australia to date in this area, and knowledge about both prevalence rates and the characteristics of offenders and victims remains limited. This exploratory study utilized police data from four Australian States to document prevalence rates of reported offenses to police, and the characteristics of adolescent violence toward parents in Australia. Between 1% and 7% of family violence reported to the police is adolescent violence toward parents. The “typical” perpetrator is a 15- to 17-year-old Caucasian young man who is generally violent toward his mother. Findings are limited by the differing police practice and policy variations between States, including the use of police discretion, leaving several questions open for further investigation. In conclusion, there is a need for change in policy and practice with regards how best to assess and respond to adolescent violence toward parents.